(untitled) (Czech Journal of International Relations, 2021)
Representative democracy is beset by a crisis of legitimacy across the world, but in Europe this crisis is compounded by the inadequacy of national governments to address citizens’ frustrations and to achieve transnational unity on common issues. How representative are national parliaments in their decision-making on EU matters? This volume investigates the relationship between the democratic institutions of the member states and those of the EU. With a focus on polity rather than policy, it looks at voting and decision-shaping mechanisms in selected member states, in particular the ‘Europeanisation’ of representative democracy at national level. It also assesses the state of parliamentary democracy at the EU level. Expert analysts share their insights into the changing nature of our political eco-systems and the (dis)connections within and between them.